The Clinical Significance and Prognostic Value of HER2 Expression in Bladder Cancer: A Meta-Analysis and a Bioinformatic Analysis - Gan, Kai; Gao, Yue; Liu, Kuangzheng; Xu, Bin; Qin, Weijun (Frontiers in Oncology, 2021)
Objective Human Epidermal Growth Factor Receptor 2 (HER2) is highly expressed in multiple malignancies and associated with patients’ prognosis, but its role in bladder cancer (BCa) remains elusive. We conducted this meta-analysis to explore the clinical significance and prognostic value of HER2 in BCa. Methods PubMed was searched for studies published between January 1, 2000 and January 1, 2020. The odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95%CIs) were used to investigate the relationship between HER2 and BCa pathological features. TCGA was mined for the information regarding as well. Results Our study included 14 articles enrolling 1398 people. Expression of HER2 is higher in bladder cancer than in normal tissues. HER2 over-expression is associated with CIS, multifocal tumor, large tumor size, high tumor stage and grade, lymph node metastasis, progression, recurrence and papillary tumor. We could not find a significant association between HER2 expression and survival time in BCa patients. Conclusions Our meta and bioinformatic analysis indicated that HER2 expression was related to pathological malignancy and poor prognosis in BCa.